2024
DOI: 10.1126/science.adn0558
|View full text |Cite|
|
Sign up to set email alerts
|

Spin-mediated promotion of Co catalysts for ammonia synthesis

Ke Zhang,
Ang Cao,
Lau Halkier Wandall
et al.

Abstract: Over the past two decades, there has been growing interest in developing catalysts to enable Haber-Bosch ammonia synthesis under milder conditions than currently pertain. Rational catalyst design requires theoretical guidance and clear mechanistic understanding. Recently, a spin-mediated promotion mechanism was proposed to activate traditionally unreactive magnetic materials such as cobalt (Co) for ammonia synthesis by introducing hetero metal atoms bound to the active site of the catalyst surface. We combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Combining Co with transition metals (i.e., Mo, Fe, Re) modulates the catalytic performance in ammonia synthesis. The association of Co with Mo in Co 3 Mo 3 N resulted in a substantial increase in performance compared to the individual components [synthesis rate of 330–652 μmol h –1 g –1 at 400 °C and atmospheric pressure and weight hourly space velocity (WHSV) of 9000 mL g –1 h –1 ]. , The presence of both, Co and Mo, in the (111) termination plane leads to an improved nitrogen binding energy (BE) . New insights from density functional theory (DFT) calculations and 15 N/ 14 N isotopic exchange studies have highlighted the role of nitride lattice nitrogen in ammonia synthesis via routes akin to the Mars-van Krevelen (MvK) mechanism. The effect of supports, such as CeO 2 , BaTiO 3– x H x , BaCeO 3– x N y H z , and BaCa­(NH 2 ) 2 , LaN, and/or catalytic activity promoters, such as BaO, LiH, and BaH 2 , in promoting the catalytic activity of Co for ammonia synthesis has also been studied and demonstrated the importance of modulating cobalt electronic states through electron transfer from dopants and/or support for achieving high catalytic activity at low temperatures. While supporting cobalt on electrides, hydrides, amides, nitrides, and oxynitrides holds great promise for developing alternative industrial catalysts to the H–B process, there are challenges related to (i) scalability of synthesis methods and (ii) reactivity under ambient conditions that must be addressed before successful implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Combining Co with transition metals (i.e., Mo, Fe, Re) modulates the catalytic performance in ammonia synthesis. The association of Co with Mo in Co 3 Mo 3 N resulted in a substantial increase in performance compared to the individual components [synthesis rate of 330–652 μmol h –1 g –1 at 400 °C and atmospheric pressure and weight hourly space velocity (WHSV) of 9000 mL g –1 h –1 ]. , The presence of both, Co and Mo, in the (111) termination plane leads to an improved nitrogen binding energy (BE) . New insights from density functional theory (DFT) calculations and 15 N/ 14 N isotopic exchange studies have highlighted the role of nitride lattice nitrogen in ammonia synthesis via routes akin to the Mars-van Krevelen (MvK) mechanism. The effect of supports, such as CeO 2 , BaTiO 3– x H x , BaCeO 3– x N y H z , and BaCa­(NH 2 ) 2 , LaN, and/or catalytic activity promoters, such as BaO, LiH, and BaH 2 , in promoting the catalytic activity of Co for ammonia synthesis has also been studied and demonstrated the importance of modulating cobalt electronic states through electron transfer from dopants and/or support for achieving high catalytic activity at low temperatures. While supporting cobalt on electrides, hydrides, amides, nitrides, and oxynitrides holds great promise for developing alternative industrial catalysts to the H–B process, there are challenges related to (i) scalability of synthesis methods and (ii) reactivity under ambient conditions that must be addressed before successful implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia (NH 3 ), as the essential chemical feedstock of pharmaceutical manufacturing, fertilizer production, energy supply, etc ., plays an important role in global energy and agricultural production. 1,2 At present, industrial-scale NH 3 synthesis is dominated by the energy-intensive Haber–Bosch (H–B) process. However, the H–B process requires high temperature (400–500 °C) and high pressure (150–300 atm), leading to the consumption of 2% of the world's annual energy output and 400 Mt of carbon dioxide emission per year.…”
Section: Introductionmentioning
confidence: 99%
“…Nørskov and co-workers found that the new promoters of Li, Ba, Ca, and La are related to the spin polarization of Co active sites, which accelerate the spin polarization of the adjacent Co for N 2 dissociation and reduce spin moment of the Co active center. Meanwhile, Nørskov and Chorkendorff recently found that the electron transfer from the La promoter to the Co active site quenches the spin moment of the nearby Co atoms, which turns out to stabilize the transition state more than the N adsorption energy and improves the ammonia synthesis . The role of the electron transfer and the residual cation has been mixed up due to the contiguous promoters and catalysts.…”
mentioning
confidence: 99%
“…Meanwhile, Nørskov and Chorkendorff recently found that the electron transfer from the La promoter to the Co active site quenches the spin moment of the nearby Co atoms, which turns out to stabilize the transition state more than the N adsorption energy and improves the ammonia synthesis. 32 The role of the electron transfer and the residual cation has been mixed up due to the contiguous promoters and catalysts. The noncontact method of promoters and catalysts via the conductive substrates could somehow separate the two effects and modulate the spin state of a catalyst accurately through electron transfer.…”
mentioning
confidence: 99%